An Analysis of Translation of Idiomatic Expression in "The Perfect Date" Movie - Aida Aulia; Dede Rohadi Fajri; Hendra Hendra (Journal of English Language Teaching and Literature (JELTL), 2023)
The objective of this research is to analyze the translation of idiomatic expression in the movie titled The Perfect Date. The aims of the research are: (1) to find out what types of strategies applied in translating idiomatic expression from English to Indonesian in the subtitle of The Perfect Date movie, and (2) to find out what types of meaning equivalence found in the translation of idiomatic expression in The Perfect Date movie. Moreover, the researcher applied content analysis method using theories by Krippendorff to conduct the analysis. To answer the first problem in the formulated question, the researcher used theory from Mona Baker. The study found that 30 expressions are commonly used in The Perfect Date movie. The findings of the study are divided into four categories based on idiom translation strategies. The result shows there are 4 idioms translated using similar meaning and form, 1 idioms translated using similar meaning but dissimilar form, 24 idioms translated using translation by paraphrase, and 1 idiom translated using translation by omission. Translation by paraphrase is the most frequently used of translation strategies in the movie. To answer the second problem in the formulated question, the researcher used theory from Eugene A. Nida. The 30 idiomatic expressions are classified into two types of meaning equivalence. There are 4 idioms classified using formal equivalence and 26 idioms classified using dynamic equivalence. However, dynamic equivalence is the most frequently used of meaning equivalence in the movie.